Mesenchymal stem cell–derived small extracellular vesicles enhance the therapeutic effect of retinal progenitor cells in retinal degenerative disease rats - Chunge Ren; Min Chen; Bangqi Ren; Yuxiao Zeng; Qiang Tan; Qiyou Li; Xue Zhang; Yajie Fang; Yixiao Zhou; Weitao Zhang; Fang Chen; Baishijiao Bian; et al. (Neural Regeneration Research)
Our previous study demonstrated that combined transplantation of bone marrow mesenchymal stem cells and retinal progenitor cells in rats has therapeutic effects on retinal degeneration that are superior to transplantation of retinal progenitor cells alone. Bone marrow mesenchymal stem cells regulate and interact with various cells in the retinal microenvironment by secreting neurotrophic factors and extracellular vesicles. Small extracellular vesicles derived from bone marrow mesenchymal stem cells, which offer low immunogenicity, minimal tumorigenic risk, and ease of transportation, have been utilized in the treatment of various neurological diseases. These vesicles exhibit various activities, including anti-inflammatory actions, promotion of tissue repair, and immune regulation. Therefore, novel strategies using human retinal progenitor cells combined with bone marrow mesenchymal stem cell–derived small extracellular vesicles may represent an innovation in stem cell therapy for retinal degeneration. In this study, we developed such an approach utilizing retinal progenitor cells combined with bone marrow mesenchymal stem cell–derived small extracellular vesicles to treat retinal degeneration in Royal College of Surgeons rats, a genetic model of retinal degeneration. Our findings revealed that the combination of bone marrow mesenchymal stem cell-derived small extracellular vesicles and retinal progenitor cells significantly improved visual function in these rats. The addition of bone marrow mesenchymal stem cell–derived small extracellular vesicles as adjuvants to stem cell transplantation with retinal progenitor cells enhanced the survival, migration, and differentiation of the exogenous retinal progenitor cells. Concurrently, these small extracellular vesicles inhibited the activation of regional microglia, promoted the migration of transplanted retinal progenitor cells to the inner nuclear layer of the retina, and facilitated their differentiation into photoreceptors and bipolar cells. These findings suggest that bone marrow mesenchymal stem cell–derived small extracellular vesicles potentiate the therapeutic efficacy of retinal progenitor cells in retinal degeneration by promoting their survival and differentiation.